Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nano11051308
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Gum Arabic Functionalized Iron Hydroxide Nanoparticles Embedded Cellulose Paper for Packaging of Paneer

Abstract: Recently, the interest of scientists has turned towards eco-friendly metal nanoparticles due to their distinctive physicochemical properties that have been used in several biochemical and food applications, including drug and bioactive component delivery, sensing of food pathogenic bacteria, imaging techniques, and theranostics. Therefore, this study aimed to fabricate gum arabic stabilized iron hydroxide nanoparticles (IHNPs) using the co-precipitation process and to develop nanoparticles decorated antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…After the reduction of sulfate to sulfide, 50 mL supernatant from 300 mL anaerobic sludge was added to 50 mL of 1 mol L −1 copper(II) sulfate pentahydrate solution (CuSO 4 .5H 2 O) while stirring for 7 days. The sulfide produced by the anaerobic sludge reacted with the copper(II) and precipitated as CuS to form biologically synthesized CuS NPs (CuS‐Bio NPs) (Eqn (2)): 26,27 CuSO4.5H2O+SCuS+5H2O+SO2+normalO2 …”
Section: Methodsmentioning
confidence: 99%
“…After the reduction of sulfate to sulfide, 50 mL supernatant from 300 mL anaerobic sludge was added to 50 mL of 1 mol L −1 copper(II) sulfate pentahydrate solution (CuSO 4 .5H 2 O) while stirring for 7 days. The sulfide produced by the anaerobic sludge reacted with the copper(II) and precipitated as CuS to form biologically synthesized CuS NPs (CuS‐Bio NPs) (Eqn (2)): 26,27 CuSO4.5H2O+SCuS+5H2O+SO2+normalO2 …”
Section: Methodsmentioning
confidence: 99%
“…A time–kill study was performed by the method followed by Chawla et al [ 26 ]. Herein, 100 µL of flower extract solution was used for all pathogenic microbial strains.…”
Section: Methodsmentioning
confidence: 99%
“…Moisture and N-H bonds in proteins are responsible for amide I, amide II, and nucleic acids attributed to the region between 1750 and 1500 cm −1 , according to the study of Andrade et al [ 32 ]. Chawla et al [ 4 ] reported that the spectral fingerprint for AGP glycoprotein or carbohydrate is the region between 1200 and 800 cm −1 . Consequently, Manhivi et al [ 34 ] investigated the functional groups of mucilage extracted from taro and cactus.…”
Section: Characterization Of Taro Mucilagementioning
confidence: 99%
“…Therefore, interest in plant-derived viscous polysaccharides, including mucilage and gums, has been increasing in the food, pharmaceutical, and other industries due to their diverse functional properties, such as emulsifying, binding, coating, gelling, thickening, and stabilizing properties [ 3 ]. Furthermore, mucilage is an eco-friendly, cost-effective, edible polysaccharide and is mainly extracted from living organisms, e.g., bacteria, fungi, plants, animals, and algae [ 4 ]. Among the plant kingdom, flaxseed, taro, chia seed, psyllium, basil seed, tamarind seeds, and okra are the richest sources of mucilage.…”
Section: Introductionmentioning
confidence: 99%